Clostridium difficile and cystic fibrosis: management strategies and the role of faecal transplantation. (March 2018) - Dunwoody, Roisin; Steel, Alan; Landy, Jonathan; Simmonds, Nicholas
Summary: Clostridium difficile is a bacterial infection that colonises the gut in susceptible hosts. It is associated with exposure to healthcare settings and antibiotic use. It could be assumed that cystic fibrosis (CF) patients are a high-risk group for C.difficile . However, despite high carriage rates, CF patients have low rates of active disease. There are guidelines for the treatment of C.difficile, however little is published specific to treating C.difficile in CF. This article provides an overview of the current management strategies for C.difficile in CF, including a description of the first faecal transplantation in this patient population.